2013
DOI: 10.1021/am401779p
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically Robust NiFe2O4 Nanofibers as High Capacity Li-Ion Battery Anode Material

Abstract: In this work, the electrochemical performance of NiFe2O4 nanofibers synthesized by an electrospinning approach have been discussed in detail. Lithium storage properties of nanofibers are evaluated and compared with NiFe2O4 nanoparticles by galvanostatic cycling and cyclic voltammetry studies, both in half-cell configurations. Nanofibers exhibit a higher charge-storage capacity of 1000 mAh g(-1) even after 100 cycles with high Coulmbic efficiency of 100% between 10 and 100 cycles. Ex situ microscopy studies con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
161
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(169 citation statements)
references
References 36 publications
8
161
0
Order By: Relevance
“…Among them, NiFe 2 O 4 nano fibers synthesized by an electrospinning approach exhibit a higher charge-storage capacity of 1000 mAh g À1 even after 100 cycles with high Coulombic efficiency of 100 % between 10 and 100 cycles at the current density of 100 mA g À1 in the voltage range 0.005-3 V [629]. This is by far the best result obtained with this compound.…”
Section: Ternary Metal Oxides With Spinel Structurementioning
confidence: 83%
“…Among them, NiFe 2 O 4 nano fibers synthesized by an electrospinning approach exhibit a higher charge-storage capacity of 1000 mAh g À1 even after 100 cycles with high Coulombic efficiency of 100 % between 10 and 100 cycles at the current density of 100 mA g À1 in the voltage range 0.005-3 V [629]. This is by far the best result obtained with this compound.…”
Section: Ternary Metal Oxides With Spinel Structurementioning
confidence: 83%
“…The energy density of LIBs mainly depends on the electrode materials. Due to a number of materials being investigated as anode in LIBs (Cherian et al 2013a;Jibin et al 2012), there are lots of possibilities (Roy and Srivastava 2015). Presently, graphite (theoretical capacity *372 mAh/g) is the commonly used anode material in commercial LIBs due to its good cyclability (van Schalkwijk and Scrosati 2007;Wu et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These nanofibers can be converted into carbon nanofibers or ceramic nanofibers depending upon polymer, additives and heat treatment conditions. Numerous binary and ternary oxide materials with fibrous (Cherian et al 2013a), nuggets (Viet et al 2009) and rice morphology (Shengyuan et al 2011;Zhu et al 2012) has been synthesized using combination of electrospinning and heat treatment and found application as lithium ion battery materials. Selection of polymer plays important role in deciding morphology of nanomaterial after electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…21 Iron-based spinel oxides, like Co 3 O 4 , were more stable during discharge/charge process. 10,14,15 However, cobalt is toxic and expensive because of comprising very few metal of the Earth's crust. 22 It is desirable to be made to replace Co in Co 3 O 4 by other cheaper and alternative elements which are friendly to environment like MCo 2 O 4 (M ¼ Zn, Cu, Ni, Mg, Fe and Mn) 11,18,20,[22][23][24][25][26] generally having higher reversible capacity 27 by concluded that metals with inverse spinel structure can be incorporated with more Li ions, compared to mixed and normal spinel.…”
Section: Introductionmentioning
confidence: 99%
“…22 It is desirable to be made to replace Co in Co 3 O 4 by other cheaper and alternative elements which are friendly to environment like MCo 2 O 4 (M ¼ Zn, Cu, Ni, Mg, Fe and Mn) 11,18,20,[22][23][24][25][26] generally having higher reversible capacity 27 by concluded that metals with inverse spinel structure can be incorporated with more Li ions, compared to mixed and normal spinel. 15,28 Various chemical and physical methods have been adopted for the preparation of these metal oxides. [47][48][49][50][51][52][53][54] and some Li + diffusion problems which will cause worse electrochemical preference such as voltage hysteresis and spinel broken spinel lattice.…”
Section: Introductionmentioning
confidence: 99%